Influences of Green Management Policies and Sustainability Practices on Reputation: The Case of International Bank of Azerbaijan (IBA). - Talibova, Sariyya (ADA University, 2022)
In order to reduce their environmental effect, corporations have come under increasing pressure over past few decades to take full responsibility for their business activities. These green processes that businesses are using to implement green practices have evolved as a result of growing stakeholder demands and pressures. Thus, a total effect of adopting various green practices on a firm's corporate reputation is examined in this thesis. A success of each of these activities is evaluated in relation to an organization's corporate reputation. Investigated is degree to which various environmental drivers, non-coercive pressures, such as customer pressures have an impact on corporate reputation as well as what is the impact of the green management practices on the corporate reputation. To that end, both qualitative and quantitative analysis were carried out. I have applied a qualitative method of analyzing results of survey results relating results with findings from review of previous literature on this particular topic. Our findings from qualitative study indicate that customers in Azerbaijan have increased their environmental awareness and they evaluate individual businesses based on their environmental, social practices, and green management strategies. A majority of people in Azerbaijan take environmental character of products into consideration when they purchase products according to results of our survey. What regards the quantitative study, the effect of green management practices of the International Bank of Azerbaijan on employees' perception of corporate reputation was examined. In this context, 84 responses consisting of 23 survey questions were collected from different departments of the International Bank of Azerbaijan. The measurement scales of green management practices and corporate reputation scales were adopted from DesJardin (2005) and Fombrun et. al. (2000), respectively. The data obtained were analyzed and interpreted using the STATA statistical software package. For both scales, validity and reliability analyses were performed and explanatory and confirmatory factor analysis was applied to test the validity of the model, and then path analysis was performed for hypothesis tests. As a result of the quantitative study, it was determined that green management practices variable has a positive significant impact on perceived corporate reputation.
Keywords: Green management.; Corporate reputation.; International Bank of Azerbaijan.; Business